Analisis Pemberitaan Pilgub Jatim 2024 Di Media Online Tribunjatim.com - Moch Nurcholis Majid; Dea Fatra Nur Laili (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2025)
This research aims to analyze the framing in the coverage of the 2024 East Java gubernatorial election in the 18 November 2024 edition of TribunJatim.com, with a focus on the latest debate discussing economic and infrastructure issues. Using Robert N. Entman's framing theory, this research identifies how the media defines problems, diagnoses their causes, makes moral decisions, and emphasizes solutions. The results of the analysis show that TribunJatim.com frames development and economic problems as the main issue, with solutions that focus on equitable development policies. This research provides insight into the role of the media in shaping public opinion regarding the 2024 East Java gubernatorial election.